Do Extent of Resection and Tumor Volume affect the Overall Survival of Anaplastic Astrocytoma? A Retrospective Study from a Single Center - Chaulagain, Dipak; Smolanka, Volodymyr; Smolanka, Andriy; Havryliv, Taras (Open Access Macedonian Journal of Medical Sciences, 2022)
Introduction: Anaplastic astrocytoma (AA) is a rare brain neoplasm that belongs to grade III gliomas according to the World Health Organization (WHO) classification. It represents only 6% of all Central Nervous System (CNS) malignancies, yet; it is associated with low survival rates. We aim to identify the survival rate after tumor resection from 10 years of experience. We also wish to determine the effect of pre and post-operative tumor volumes on the overall survival (OS). Methods: We retrospectively reviewed the records of patients with anaplastic astrocytoma who had surgery between January 2010 and January 2020. Based on Magnetic resonance imaging (MRI) results obtained < 72 hours after surgery, the Extent of Resection (EOR) was calculated by pre-op volume – post-op volume/pre-op volume*100% and classified into five categories. 1)>99% - Gross total resection (GTR) 2) 91-99% as Near-total resection (NTR) 3) 70-90% as Sub-total resection (STR) 4) <70% as Partial resection (PR) and 5) Biopsy. A multivariate proportional hazards regression analysis assessed the independent association of EOR and subsequent OS. Results: 34 patients were finally included in our analysis. The median survival time for all patients was 24.4 months, whereas the histopathological type of AA like IDH mutant was 32 months, and IDH wild type was 16.1 months as OS time. We stratified the observed survival durations for the patients according to the EOR into 5 different classes. We found that the EOR didn’t affect the overall median survival. Regression analysis showed no statistically significant association between the pre or post-operative tumor volume and the OS time. Conclusion: Anaplastic astrocytoma is a tumor that carries a poor diagnosis. Gross total resection is essential to increase patients expected survival time. Unfortunately, the extent of tumor resection and tumor volume isn’t correlated with the survival time for patients.